2016
DOI: 10.1007/s00705-016-2761-7
|View full text |Cite
|
Sign up to set email alerts
|

Geographically driven adaptation of chilli veinal mottle virus revealed by genetic diversity analysis of the coat protein gene

Abstract: Chilli veinal mottle virus (ChiVMV) is an important plant pathogen with a wide host range. The genetic structure of ChiVMV was investigated by analyzing the coat protein (CP) genes of 87 ChiVMV isolates from seven Asian regions. Pairwise F ST values between ChiVMV populations ranged from 0.108 to 0.681, indicating a significant spatial structure for this pathogen. In phylogeny-trait association analysis, the viral isolates from the same region tended to group together, showing a distinct geographic feature. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…Here, phylogenetic analysis revealed that MpnDV haplotypes clustered according to geographical origin, except for those found in Liaoning and Shanxi provinces, likely due to long-distance migration of M. persicae nicotianae (Loxdale et al, 1993). Aphids from Liaoning may have crossed the Bohai Sea, subsequently interacting with other populations, while others might have migrated from Shanxi to Yunnan (Gao et al, 2016). From the distribution of haplotypes in the NJ tree and their locations, no significant relationship between haplotype and geographical distance was evident.…”
Section: Discussionmentioning
confidence: 74%
“…Here, phylogenetic analysis revealed that MpnDV haplotypes clustered according to geographical origin, except for those found in Liaoning and Shanxi provinces, likely due to long-distance migration of M. persicae nicotianae (Loxdale et al, 1993). Aphids from Liaoning may have crossed the Bohai Sea, subsequently interacting with other populations, while others might have migrated from Shanxi to Yunnan (Gao et al, 2016). From the distribution of haplotypes in the NJ tree and their locations, no significant relationship between haplotype and geographical distance was evident.…”
Section: Discussionmentioning
confidence: 74%
“…ChiVMV infection greatly inhibits plant growth and causes severe symptoms including mottling, distortion, and systemic necrosis ( Chung et al , 2008 ). The ChiVMV genome is a positive-sense, ssRNA of 9.7 kb, excluding the poly(A) tail ( Vijayapalani et al , 2012 ; Gao et al , 2016 ). Potyviral helper component proteinase (HCPro) is a multifunctional protein mainly involved in aphid transmission and suppression of post-transcriptional gene silencing ( Anandalakshmi et al , 1998 ; Kasschau et al , 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…The open reading frame (ORF) of ChiVMV encodes a large polyprotein, which is processed into ten functional mature proteins [2,3]. ChiVMV mainly infects solanaceous crops and has caused considerable economic losses to pepper (Capsicum annuum L.) production in Asia and Africa [4][5][6][7][8][9][10][11][12]. Moreover, it has been found highly deleterious to production of tobacco (Nicotiana tabacum L.) production since 2011 in China [13][14][15].…”
Section: Introductionmentioning
confidence: 99%